TANGGUNGJAWAB SOSIAL DAN LINGKUNGAN TERHADAP KINERJA KEUANGAN : PERAN MEDIASI KEMAMPUAN INOVASI - Salsabila, Kamilia Zulfa; Solovida, Grace Tianna (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to analyze the effect of CSR on financial performance and innovation ability, the effect of innovation ability on financial performance, and determine the mediating role of innovation ability in the relationship between CSR and financial performance of SMEs in Semarang. The data used in the study is primary data using a survey method by distributing questionnaires to 109 SMEs in Semarang. The sample used was 53 respondents. The analytical tool used is Smart PLS with partial least squares structural equation modeling (PLS-SEM) method. The results of this study indicate that CSR has no effect on financial performance, CSR has a significant effect on innovation capability, innovation capability has no effect on financial performance, and innovation capability does not mediate the relationship between CSR and financial performance. Keywords: CSR; innovation capability; financial performance